2011
DOI: 10.1523/jneurosci.0007-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Functional MRI Response Temporal Linearity via Optical Control of Neocortical Pyramidal Neurons

Abstract: The blood oxygenation level-dependent (BOLD) signal serves as the basis for human functional MRI (fMRI). Knowledge of the properties of the BOLD signal, such as how linear its response is to sensory stimuli, is essential to the design and interpretation of fMRI experiments. Here, we combined the cell-type and site-specific causal control provided by optogenetics and fMRI (opto-fMRI) in mice to test the linearity of BOLD signals driven by locally induced excitatory activity. We employed high-resolution mouse fM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
110
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(119 citation statements)
references
References 26 publications
9
110
0
Order By: Relevance
“…Specifically, we report absorption coefficients two-to threefold larger than the largest reported in a recent study of fresh and frozen brain slices (30) and about 10-fold larger than the values that Yaroslavsky et al (29) reported based on measurements taken in postmortem human tissue. Unfortunately, the ex vivo values of Yaroslavsky et al (29) have been used widely in the optogenetics literature (26,28,53,(74)(75)(76)(77)(78) because, before the present study, techniques were not available for in vivo measurements of light propagation in living brain tissue across the full spectrum of visible light. The absorption coefficient that we determined for red light falls squarely within the range of reported values from extracted tissue and one in vivo study (i.e., μ a = 0.20-4.5 cm −1 ) (29, 30, 79-83).…”
Section: Discussionmentioning
confidence: 95%
“…Specifically, we report absorption coefficients two-to threefold larger than the largest reported in a recent study of fresh and frozen brain slices (30) and about 10-fold larger than the values that Yaroslavsky et al (29) reported based on measurements taken in postmortem human tissue. Unfortunately, the ex vivo values of Yaroslavsky et al (29) have been used widely in the optogenetics literature (26,28,53,(74)(75)(76)(77)(78) because, before the present study, techniques were not available for in vivo measurements of light propagation in living brain tissue across the full spectrum of visible light. The absorption coefficient that we determined for red light falls squarely within the range of reported values from extracted tissue and one in vivo study (i.e., μ a = 0.20-4.5 cm −1 ) (29, 30, 79-83).…”
Section: Discussionmentioning
confidence: 95%
“…The power was ϳ700 mW/mm 2 at brain surface. Based on previous work addressing light spreading and scattering in brain tissue (Aravanis et al, 2007;Kahn et al, 2011), the laser power at the depth of layer 5 (800 m, where most ChR2-YFP-labeled neuronal cell bodies were found) was expected to be ϳ6 mW/mm 2 ; however, light levels at superficial dendrites were likely much higher. Laser power for ChR2 stimulation was adjusted (1-5 mW) following one to two pilot trials to obtain a Ն0.5 mV peak EEG response, which was measured with a surface electrode.…”
Section: Methodsmentioning
confidence: 99%
“…To obtain information from different cortical depths, a silicon optrode (A1x16-3 mm-50-413-Op16, NeuroNexus Technologies) was used for recording LFP and multiunit activity (MUA) and ChR2 stimulation in eight mice (Kravitz et al, 2010;Kahn et al, 2011). The optrode contained 16 413 m 2 recording sites (0.7-1.2 M⍀ impedance at 1 kHz), arranged linearly with 50 m spacing between each site.…”
Section: Methodsmentioning
confidence: 99%
“…Optical stimulus parameters consisted of three parameter groups: The first one was four pulse durations (5, 10, 30, and 50 ms) with a fixed power of 2.5 mW and a frequency of 8 Hz. The second group covered four light frequencies within the native firing rate of excitatory glutamatergic cells (3,8,12, and 20 Hz) with a fixed power of 2.5 mW and a pulse duration of 30 ms; and the third group included five light power levels (1, 2.5, 5, 10, and 20 mW) with a fixed frequency of 8 Hz and a pulse duration of 30 ms. Since one combination (8 Hz, 2.5 mW, and 30 ms) was common for all three modulation studies, a total of 11 different light stimulation parameters were used.…”
Section: Stimulationmentioning
confidence: 99%